Comparing redistributive efficiency of tax-benefit systems in Europe - Daniela Mantovani (University of Essex, Institute for Social and Economic Research (ISER), 2018)
In empirical analysis, the Kakwani index is the most frequently used indicator for comparing progressivity across countries and over time. The Kakwani is often assumed to measure to what extent a policy design is targeted to the poor. It has, however, a major drawback: it is not defined for net tax incidence - that is, the whole system of taxes and benefits. Moreover, it is defined over different intervals for different pre-tax income distributions and different average tax rates. This paper proposes an extension to Kakwani index based on the concept of relative redistributive efficiency that is not affected by these drawbacks. The Redistributive Efficiency index was compared to the Kakwani index for taxes/benefits in EU countries by using Euromod baselines. In addition, the Redistributive Efficiency index was computed on the whole tax-benefit system; that is, taxes and benefits were evaluated together. Only Ireland and the UK combine high levels of redistributive efficiency with a relevant amount of tax revenues and social expenditures. They obviously obtain very high redistribution, above 15 points. Most of the countries considered show an intermediate level of redistribution (between 7 and 12 points), but with a different mix. A group of Central and Northern European countries plus Slovenia and Hungary combine medium levels of redistributive efficiency and medium size, while some Southern European countries (Spain and Portugal) and new members compensate a rather low amount of transfer and taxes with quite high levels of efficiency. The remaining new member states and Southern EU countries show a very low level of redistribution, below 7 points. Interestingly, they vary in the level of tax burden and of resources devoted to benefits but all of them show a poor Redistributive Efficiency. This suggests that low Redistributive Efficiency plays a key role in explaining why certain countries perform a limited amount of redistribution.
Keywords: C00; D31; H20; I38; 330; Income Redistribution; Progressivity; Microsimulation; EUROMOD